Ethnobotanical survey of anti-constipation medicinal plants used in Sikonge District, Tanzania - Kacholi, David Sylvester; Amir, Halima Mvungi (Ethnobotany Research and Applications, 2024)
Background: Constipation is a common gastrointestinal disorder in most low-and middle-income countries, including Tanzania. The disorder causes economic burdens to many societies in the country. Most of the locals in Tanzania depend on medicinal plants (MPs) to treat various ailments, including constipation. This study aimed to document MPs used by Nyamwezi traditional health practitioners (NTHPs) to manage constipation in Sikonge district, Tanzania. Methods: This study was conducted between August and October 2020 in Sikonge district. The ethnobotanical data on MPs used to treat constipation, plant part(s) used, mode of preparation, and route administration of remedies were collected from twenty-three (23) NTHPs using a semi-structured questionnaire. The aim of the study was communicated to all NTHPs, and their consent was requested before interviewing them. Results: The study documented 15 MPs belonging to 12 families and 14 genera. Euphorbiaceae was the wealthiest family with three MPs. Tree (40%) was the dominant life form utilised for herbal remedies preparations, and most MPs (67%) were collected from the wild areas. Roots (44%) were the most utilized plant part, decoction (73%) was the preferred remedy preparation method, and oral administration (93%) was the most used route in administering remedies. Euphorbia hirta Oliv. (81%), Ricinus communis L. (76%), Euphorbia candelabrum Welw. (67%), and Clerodendrum capitatum (Willd.) Schumach. (62%) were frequently mentioned by the NTHPs as the most widely used anti-constipation MPs in the area. Conclusion: The study discloses that MPs are vital for primary health care needs in most rural areas in Tanzania. Moreover, it offers evidence for forthcoming pharmacological studies to discover effective and affordable novel drugs against constipation. Keywords: Ethnobotany, ethnomedicine, constipation, digestive disorders, gastrointestinal, herbal remedies, Nyamwezi healers, Tabora region